2015
DOI: 10.1088/0964-1726/24/9/094007
|View full text |Cite
|
Sign up to set email alerts
|

Structural modelling of a compliant flexure flow energy harvester

Abstract: CHATTERJEE, PUNNAG. Structural Modeling of a Compliant Flexure Flow Energy Harvester. (Under the supervision of Dr. Matthew Bryant). This thesis presents the concept of a flow-induced vibration energy harvester based on a one-piece compliant flexure structure. This energy harvester utilizes the aeroelastic flutter phenomenon to convert flow energy to structural vibrational energy and to electrical power output through piezoelectric transducers. This flexure creates a discontinuity in the structural stiffness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Exploiting aeroelastic vibration phenomenon to harvest energy from ambient airflow has been the subject of considerable interest recently [4][5][6][7][8][9]. It has been shown that aeroelastically excited oscillators can have competitive efficiencies and power densities with similarly sized traditional electromagnetic turbines at low operating wind speeds [10], and can offer the additional benefits of simple, solid-state construction.…”
Section: Introductionmentioning
confidence: 99%
“…Exploiting aeroelastic vibration phenomenon to harvest energy from ambient airflow has been the subject of considerable interest recently [4][5][6][7][8][9]. It has been shown that aeroelastically excited oscillators can have competitive efficiencies and power densities with similarly sized traditional electromagnetic turbines at low operating wind speeds [10], and can offer the additional benefits of simple, solid-state construction.…”
Section: Introductionmentioning
confidence: 99%
“…Fluidic energy is a kind of clean energy, such as compressed air and waves. Compressed air energy has attracted great attention due to its kinetic energy induced by piezoelectric materials [12][13][14][15]. Bryant et al demonstrated a sealed spaced array of aeroelastic flutter energy harvesters, and the experimental result showed that the harvesters can extract additional energy from the wake of upstream harvesters, causing larger oscillation amplitudes and higher power output in the trailing devices [16].…”
Section: Introductionmentioning
confidence: 99%